PENINGKATAN PENERIMAAN DIRI DAN GAMBARAN DIRI WANITA MENOPAUSE DENGAN ACCEPTANCE AND COMMITMENT THERAPY - Chindy Maria Orizani (STIKes Adi Husada, 2015)
Menopausal phase could impact the physical, psychological, social, economic, spiritual and quality of life. Changes appear on the physical aspects could cause decreasing self-image in menopausal women, whereas the psychological changes that arise sometimes menopausal women experience a decrease in self-acceptance. The aim of this study is to prove the existence of increased acceptance and self-image menopausal women with Acceptance and Commitment Therapy. The design used is Quasy Experiment Pre-posttest with Controlled Group Design. The sample was menopausal women who are willing to become respondents as many as 40 people, divided into two groups: a control group of 20 people and 20 people treated group. Sampling technique using consecutive sampling. The independent variable for the provision of Acceptance and Commitment Therapy is divided into two sessions of four meetings (1x meeting two sessions). The dependent variable is self-acceptance and self-image menopausal women. Measuring instruments used in the form of a questionnaire. Analysis of data used computer software. The majority of respondents were married women, Muslim, Javanese, recent education junior high school and not working. The results proved statistically there was increasing acceptance between control and treatment groups (p = 0.000). Self-image measurement results proved no increase between control and treatment groups (p = 0.000). Acceptance and Commitment Therapy is highly effective for improving acceptance and self image in menopausal women. The active role of the respondents strongly supported upon the success of therapy and need the support of her husband and peers. Masa menopause dapat berdampak pada aspek fisik, psikologis, sosial, ekonomi, spiritual dan kualitas hidup seseorang. Perubahan yang muncul pada aspek fisik mengakibatkan penurunan gambaran diri wanita menopause, sedangkan perubahan psikologis yang muncul terkadang wanita menopause mengalami penurunan penerimaan diri. Tujuan dari penelitian ini adalah membuktikan adanya peningkatan penerimaan dan gambaran diri wanita menopause dengan Acceptance and Commitment Therapy. Desain yang digunakan adalah Quasy Experiment Pre-Posttest with Controlled Grup Design. Sampel penelitian ini adalah wanita menopause yang bersedia menjadi responden sebanyak 40 orang, dibagi menjadi dua grup, yaitu 20 orang grup kontrol dan 20 orang grup perlakuan. Teknik sampling menggunakan consecutive sampling. Variabel independen berupa pemberian Acceptance and Commitment Therapy empat sesi dibagi menjadi dua pertemuan (1x pertemuan dua sesi). Variabel dependen yaitu penerimaan diri dan gambaran diri wanita menopause. Alat ukur yang digunakan berupa kuesioner. Analisis data menggunakan software computer. Mayoritas responden adalah wanita menikah, beragama Islam, suku Jawa, pendidikan terakhir smp dan tidak bekerja. Hasil penelitian secara statistik terbukti ada peningkatan penerimaan diri antara grup kontrol dan perlakuan (p=0,000). Hasil pengukuran gambaran diri terbukti ada peningkatan antara grup kontrol dan perlakuan (p=0,000). Acceptance and Commitment Therapy ini sangat efektif untuk meningkatkan penerimaan dan gambaran diri pada wanita menopause. Peran aktif responden sangat mendukung kesusksesan terapi dan butuh dukungan dari suami dan teman sebaya. DOWNLOAD FULL TEXT PDF >>